Targeted Poverty Alleviation and Pro-Poor Growth: Evidence from China’s Practice and Experience - Li, Shi; Shen, Yangyang (Journal of Income Distribution®, 2022)
This article assesses the pro-poor growth effect in China’s rural populations over the period 2007–2018 using the strict pro-poor index proposed by Nanak Kakwani. The results show that while China’s rural areas did not experience strictly defined pro-poor growth between 2007–2013, a contemporary pro-poor effect was observed during which Targeted Poverty Alleviation (TPA) policies were implemented. The conclusion is robust in the dimensions of income and expenditure and non-income well-being. Through a heterogeneity analysis, this article finds differences in pro-poor growth among various groups. In particular, poor women, seniors, children, and geographic areas (such as western China) benefited more during the targeted poverty-alleviation policy period than their counterparts. Finally, we use Kakwani’s shared prosperity index to show that China is actively making more positive efforts and preparations towards attaining commonly shared prosperity.